Global groundwater situation: opportunities and challenges - Shah, Tushar et al. (2001)
It is widely predicted that problems of groundwater overexploitation will become more acute and widespread. The challenge then is not merely supply-side innovations but to set in place a range of corrective mechanisms that would involve a shift from resource development towards resource management. Countries with severe groundwater depletion still remain hampered however by lack of information. Not only is there no systematic monitoring of groundwater occurrence and draft, but management of such resources has for long remained in private informal channels, with public agencies playing only an indirect role. - Reproduced
Keywords: Groundwater